Suitability of Centella asiatica (pegaga) as a food source for rearing Spodoptera litura (F.) (lepidoptera: noctuidae) under laboratory conditions - Javar, Saeedeh; Sajap, Ahmad Said; Mohamed, Rozi; Lau, Wei Hong (De Gruyter Open, 2013)
When conducting entomological research, it is necessary to have a sufficient quantity of the desired pest. One of the pests commonly used in research is Spodoptera litura. Mass rearing of herbivorous caterpillars like S. litura requires large amounts of a suitable food source. Hence, the use of an easy-to-grow host plant would be most practical and reasonable. Centella asiatica known as ‘pegaga’ grows easily, produces plenty of leaves, and is available throughout the year in Malaysia. The suitability of C. asiatica as a food source for S. litura was evaluated by studying the biology of this pest on excised C. asiatica leaves, under laboratory conditions. S. litura completed its whole life cycle in 29 to 35 days. The mean pupal weight and the average number of eggs laid by a single female were 0.341 g and 1,930 eggs, respectively. Daily monitoring of the larval development stages as well as analysis on the width of head capsules, revealed the existence of six instars during the larval stages of S. litura. The cumulative survival rate for immature developmental stages was 80%, while the stage-specific survivorship was over 90%. This study demonstrated the use of ‘pegaga’ as a suitable new food source for when rearing S. litura larvae in the laboratory.